IMPACT OF EDUCATIONAL INTERVENTIONS ON PSYCHOLOGICAL DISTRESS DURING ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION: A RANDOMIZED STUDY. - Marco Cioce; Franziska Michaela Lohmeyer; Rossana Moroni; Marinella Magini; Alessandra Giraldi; Paola Garau; Maria Carola Gifuni; Vezio Savoia; Danilo Celli; Stefano Botti; Gianpaolo Gargiulo; Francesca Bonifazi; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background